A review of gallium nitride power device and its applications in motor drive - Ding, Xiaofeng; Zhou, Yang; Cheng, Jiawei (CES Transactions on Electrical Machines and Systems, 2019)
Wide band-gap gallium nitride (GaN) device has the advantages of large band-gap, high electron mobility and low dielectric constant. Compared with traditional Si devices, these advantages make it suitable for fast-switching and high-power-density power electronics converters, thus reducing the overall weight, volume and power consumption of power electronic systems. As a review paper, this paper summarizes the characteristics and development of the state-of-art GaN power devices with different structures, analyzes the research status, and forecasts the application prospect of GaN devices. In addition, the problems and challenges of GaN devices were discussed. And thanks to the advantages of GaN devices, both the power density and efficiency of motor drive system are improved, which also have been presented in this paper.